2022
DOI: 10.3390/sym14122607
|View full text |Cite
|
Sign up to set email alerts
|

Movie Reviews Classification through Facial Image Recognition and Emotion Detection Using Machine Learning Methods

Abstract: The critical component of HCI is face recognition technology. Emotional computing heavily relies on the identification of facial emotions. Applications for emotion-driven face animation and dynamic assessment are numerous (FER). Universities have started to support real-world face expression recognition research as a result. Short video clips are continually uploaded and shared online, building up a library of videos on various topics. The enormous amount of movie data appeals to system engineers and researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…[ 36 ] demonstrated that it could classify between baseline and high arousal and valence levels with an accuracy of 80%. Some studies have aimed to determine the specific emotion displayed by participants, achieving accuracies of 65.75% [ 9 ] and 84.72% [ 24 ]. However, these studies do not allow us to determine whether participants are in a state of stress or relaxation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 36 ] demonstrated that it could classify between baseline and high arousal and valence levels with an accuracy of 80%. Some studies have aimed to determine the specific emotion displayed by participants, achieving accuracies of 65.75% [ 9 ] and 84.72% [ 24 ]. However, these studies do not allow us to determine whether participants are in a state of stress or relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Artificial Intelligence (AI) techniques such as ML and Deep Learning (DL) has been very useful and extensively studied in recent times, allowing us to create systems capable of classifying, determining, and/or selecting different types of features within a database. By using these tools in conjunction with advanced image processing available today, work has been developed for a wide range of fields, such as facial recognition, as seen in the work of [23,24], which perform facial recognition using AI. In other cases, it has also been employed for classifications or identifications among individuals; for instance, [25] conducted ethnic identification of participants through the use of DL.…”
Section: Methodsmentioning
confidence: 99%
“…The other name is non-parametric naïve Bayes [30,31]. However, in some cases, these naïve Bayes methods did not obtain the classification performance satisfactorily [5,32], especially in corn plant disease classification [15,16].…”
Section: Introductionmentioning
confidence: 99%